A reevaluation of the role of family in immigrants' labor market activity: evidence from a comparison of single and married immigrants - Sarit Cohen-Goldner; Chemi Gotlibovski; Nava Kahana (Institute for the Study of Labor (IZA), 2009)
Previous papers tested the validity of the Family Investment Hypothesis (FIH) among immigrants by comparing the labor market outcomes of immigrant couples and native or mixed couples. Here we propose an alternative test for the FIH which is based on a comparison between married and single immigrants. The logic underlying this alternative method states that if credit constraints are binding, then only married immigrants can cross-finance their investment within the family. In order to overcome potential selection bias that would arise if unobserved characteristics that affect the marital status of the individual also affect his/her labor market outcomes, we construct a difference-in-differences estimator that exploits variation in the labor market outcomes of married and single natives. Implementation of this method using US and Israeli data leads to a rejection of the FIH in both countries.
Keywords: J22; J61; 330; Family investment model; labor supply; Migranten; Familienökonomik; Verschuldungsrestriktion; Investition; Theorie; USA; Israel